Defining active mobility through agent-based modeling visualizing urban nodes and connections of Cabanatuan City, Nueva Ecija - Roque, Trina Rose B.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2026)
This study explores how urban design interventions influence active mobility within the urban core of Cabanatuan City, Nueva Ecija, through the integration of Agent-Based Modeling (ABM) and Geographic Information System (GIS). The research defines the relationship between the built environment, socio-economic characteristics and individual travel behavior to define patterns of walking and cycling in selected urban node, specifically along Burgos Avenue and Del Pilar Street. Using ABM simulations and survey data, the study identifies urban nodes, connections, and potential routes for enhancing active transportation. Results reveal that urban form land-use diversity, socio-economic characteristic and street connectivity significantly affect active mobility choices. Lower-middle-income groups are more likely to engage in walking. The findings indicate that urban design interventions, particularly tactical urbanism, are more effective in encouraging walking than the provision of pedestrian infrastructure alone. Moreover, the presence of such interventions leads to a significant shift from motorized transport to walking, while the transition from motorized modes to cycling shows only minimal change. Simulation outcomes indicate that a 10-30% modal shift from motorized trips to walking or cycling could substantially reduce congestion and vehicle emissions. The findings affirm that compact, mixed-use neighborhoods and accessible street networks foster conditions favorable for walkability. Moreover, ABM proved effective in visualizing spatial mobility dynamics and identifying areas suitable for pedestrian infrastructure development. The study concludes that active mobility is not merely a behavioral choice but a product of the built environment's capacity to support human-centered, sustainable urban living. By combining empirical observation and computational modeling, this research provides a framework for data-driven urban design that can guide policymakers, planners, and local governments toward a more connected, sustainable urban environment.
Include appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Cities and towns -- Health aspects -- Cabanatuan City (Nueva Ecija); City planning -- Cabanatuan City (Nueva Ecija); Walkability -- Cabanatuan City (Nueva Ecija); Pedestrian areas -- Cabanatuan City (Nueva Ecija)